P346 HEALTH LITERACY ASSESSMENT AND HOSPITAL LENGTH OF STAY: A RETROSPECTIVE STUDY. (18th May 2022) - Cristofori, E; De Rinaldis, M; Iula, A; Conte, M; Cocchieri, A
Abstract: Background: Cardiovascular diseases (CDs) were the leading cause of death worldwide in 2020. The risk of increasing CD is related to low Health Literacy (HL). HL can be defined as the individual's ability to understand and process health information. Low HL has a risk ratio of 1.90 on mortality and 1.35 on readmission. A low level of HL was related to poorer use of health care services. Several inconsistencies were found about the relationship between HL and Length of stay (LOS). Although CDs are increasing because of the aging population, HL is often underestimated in the hospital setting. For this reason, HL assessment is important to identify patients at risk of poor HL. Therefore, this study aimed to describe the HL level in inpatients with CDs and to analyze the relationship between HL and LOS Method: A retrospective design was used to randomly select 134 patients with CDs in eight cardiovascular and internal medicine units of an Italian hospital from 10 January to 10 May 2021. Clinical data were collected using a nursing information system (NIS) and the hospital discharge register. Single Item Literacy Screener (SILS) was used to measure HL and was systematically reported on NIS. Results: The mean age of the sample was 71.28 (SD 13.19); 59% were male. HL's mean score was 2.43 (SD 1.2). A statistically significant linear association (Spearman's correlation coefficient) was observed between the HL score and LOS. Patients with inadequate HL were 50.7% and had a longer LOS than patients with adequate HL (mean 9.1 ± 7.1 Vs 7.2 ± 5.9 days respectively, p = 0.05). Conclusion: HL is poor and has been shown to be associated with LOS. These results should be confirmed after considering other variables through multivariate analyses. These findings suggest that the adverse effects of low HL may extend into the inpatient cardiovascular setting